Structural Characterization of a Composition Tolerant Bulk Heterojunction Blend. Issue 10 (14th March 2014) - Huang, Ye; Liu, Xiaofeng; Wang, Cheng; Rogers, James T.; Su, Gregory M.; Chabinyc, Michael L.; Kramer, Edward J.; Bazan, Guillermo C.
<x xml:space="preserve">Abstract</x> The ratio of the donor and acceptor components in bulk heterojunction (BHJ) organic solar cells is a key parameter for achieving optimal power conversion efficiency (PCE). However, it has been recently found that a few BHJ blends have compositional tolerance and achieve high performance in a wide range of donor to acceptor ratios. For instance, the X2:PC61BM system, where X2 is a molecular donor of intermediate dimensions, exhibits a PCE of 6.6%. Its PCE is relatively insensitive to the blend ratio over the range from 7:3 to 4:6. The effect of blend ratio of X2/PC61BM on morphology and device performance is therefore systematically investigated by using the structural characterization techniques of energy‐filtered transmission energy microscopy (EF‐TEM), resonant soft X‐ray scattering (R‐SoXS) and grazing incidence wide angle X‐ray scattering (GIWAXS). Changes in blend ratio do not lead to obvious differences in morphology, as revealed by R‐SoXS and EF‐TEM. Rather, there is a smooth evolution of a connected structure with decreasing domain spacing from 8:2 to 6:4 blend ratios. Domain spacing remains constant from 6:4 to 4:6 blend ratios, which suggests the presence of continuous phases with proper domain size that may provide access for charge carriers to reach their corresponding electrodes.